Cumulative Radiation Dose in Patients Admitted with Subarachnoid Hemorrhage: A Prospective Study Using a Self-Developing Film Badge - Mamourian, A.C.; Young, H.; Stiefel, M.F. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: While considerable attention has been directed to reducing the x-ray dose of individual imaging studies, there is little information available on the cumulative dose during imaging-intensive hospitalizations. We used a radiation-sensitive badge on 12 patients admitted with SAH to determine if this approach was feasible and to measure the extent of their x-ray exposure. MATERIALS AND METHODS: After obtaining informed consent, we assigned a badge to each of 12 patients and used it for all brain imaging studies during their ICU stay. Cumulative dose was determined by quantifying exposure on the badge and correlating it with the number and type of examinations. RESULTS: The average skin dose for the 3 patients who had only diagnostic DSA without endovascular intervention was 0.4 Gy (0.2–0.6 Gy). The average skin dose of the 8 patients who had both diagnostic DSA and interventions (eg, intra-arterial treatment of vasospasm and coiling of aneurysms) was 0.9 Gy (1.8–0.4 Gy). One patient had only CT examinations. There was no effort made to include or exclude the badge in the working view during interventions. CONCLUSIONS: It is feasible to incorporate a film badge that uses a visual scale to monitor the x-ray dose into the care of hospitalized patients. Cumulative skin doses in excess of 1 Gy were not uncommon (3/12) in this group of patients with acute SAH. This approach could provide a measure of the cumulative dose and is a convenient tool to quantify the effect of dose-reduction strategies. ACRAmerican College of RadiologyAP/LATanteroposterior/lateralCTACT angiographyCTPCT perfusionDSAdigital subtraction angiographyDXdiagnosticFluoro.fluoroscopyICUintensive care unitIRinterventional radiologyMCAmiddle cerebral arteryPcomAposterior communicating arteryRICAright internal carotid arterySAHsubarachnoid hemorrhageSCAsuperior cerebellar artery